Public relations in health care system - Walicka, Aneta Małgorzata (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The slowl but gradual process relying on the transformation of ‘the medical service’ into ‘the service’ has been noticed during the last few years in Poland. Health service has become ‘a commodity’, while medical estabilishments are considered to be service companies. Therefore, they are obliged to operate on market terms and conditions, which means: dealing with competition, a bitter fight for a patient, a contract and even for access to funds. As a result of so-called ‘market game’ we can observe huge marketing activities, including the activities connected with PR. The aim of this paper is to show how important is public relations in Polish Health Care System. PR is the second, next to the advertising, kind of mass promotion and at the same time is a crucial component of marketing strategy. The main aim of PR is to shape a positive image and build mutual relation, trust and cooperation. What is more, PR inspires huge confidence among receivers of a message. Moreover, as far as medical serices are concerned, PR seem to be the best and the most effective form of communication. Thanks to PR Polish Health Care System, which does not receive a positive public opinion, it can significantly improve its image. However, the activities regarding PR are still a relatively new element in Health Care System. A special attention should be drawn to the areas of PR activities that can be introduced to Polish Health Care System. Such activities as: internal PR, media relations, crisis management and lobbing are worth mentioning.